Contraband Cultures: Reframing Smuggling Across Latin America and the Caribbean (UCL Press, 2024)
Contraband Cultures presents narratives, representations, practices and imaginaries of smuggling and extra-legal or informal circulation practices, across and between the Latin American region (including the Caribbean) and its diasporas. Countering a fetishizing and hegemonic imaginary (typically stemming from the Global North) of smuggling activity in Latin America as chaotic, lawless, violent and somehow 'exotic', this book reframes such activities through the lenses of kinship, political movements, economic exchange and resistance to capitalist state hegemony.The volume comprises a broad range of chapters from scholars across the social sciences and humanities, using various methodological techniques, theoretical traditions and analytic approaches to explore the efficacy and valence of 'smuggling' or 'contraband' as a lens onto modes of personhood, materiality, statehood and political (dis)connection across Latin America. This material is presented through a combination of historic documentation and contemporary ethnographic research across the region to highlight the genesis and development of these cultural practices whilst grounding them in the capitalist and colonial refashioning of the entire region from the sixteenth century to the present day.